Genetic variability and heritability of Green Super Rice (GSR) lines resistance to Rice Ragged Stunt Virus (RRSV) and Rice Grassy Stunt Virus (RGSV) - Susanto, Untung; Nafisah, Nafisah; Rohaeni, Wage R.; Baehaki S.E.; Rahman, Sarlan Abdul; Ali, Jauhar (Indonesian Agency for Agricultural Instrument Standardization, 2020)
Brown plant hopper (BPH) is one of the main pest of rice in Indonesia and it occurred every years with fluctuate acreage. BPH is also vector of Rice Ragged Stunt Virus (RRSV) and Rice Grassy Stunt Virus (RGSV). Green Super Rice (GSR) was designed to have resistance to major pests and diseases so that it need less pesticides and thus save ro environment. GSR was developed in IRRI and China and was tested in Indonesia since 2009 until now (2019). This research was aimed to study the genetic variability and heritability of 26 selected GSR lines to RRSV and RGSV along with four check varieties. The experiment was conducted in ICRR Sukamandi and Pusakanagara Experimental Station. The experiment was arranged following randomized complete block design with three replications. Transplanting was done into 21 days old seedling into 25 cm x 25 cm planting space of 1 m x 1 m plot. BPH and virus investation was occured narturally due to BPH outbreak along the season (DS 2010). Percentage of plant showing RRSV and RGSV symtom was measured as consideration the resistance of plant to the viruses. The results showed that the tested genotypes had high genetic variability and heritability classified as medium in the resistance to RGSV. The genotypes showed low genetic variability and heritability in the resistance to RRSV. It implies that breeder effort is feasible to develop resistant lines to RGSV. HUANGHUAZHAN and HHZ 12-Y4-Y3-Y1 are consistently resistant to RGSV and can be used as donors in further plant breeding activities. The selection of resistant individuals in populations of plant breeding material recommended to be done on earlier generations for RGSV and further generation for RSSV.